Fund ownership, wealth, and risk-taking: Evidence on private equity managers - Bienz, Carsten; Thorburn, Karin S.; Walz, Uwe (Journal of Financial Intermediation, 2023)
Private equity (PE) managers are required to invest their own money in the funds they manage. We examine the incentive effects of this ownership on the delegated acquisition decision. A simple model shows that PE managers select less risky firms and use more debt, the higher their ownership. We test these predictions for a sample of Norwegian PE funds, using managers’ wealth to capture their relative risk aversion. As predicted, the target company’s cash-flow risk decreases and leverage increases with the manager’s ownership scaled by wealth. Moreover, the overall portfolio risk decreases with ownership, mitigating widespread concerns about excessive risk-taking.